Utilization of cardiopulmonary bypass at radical nephrectomy for renal cell carcinoma with tumour thrombus - Chalairat Suk‐Ouichai; Mitchell M. Huang; Clayton Neill; Christopher K. Mehta; Ashley E. Ross; Shilajit D. Kundu; Kent T. Perry Jr; Duc T. Pham; Hiten D. Patel (BJUI Compass)
Abstract Objectives The objective of this study is to evaluate preoperative factors associated with cardiopulmonary bypass (CPB) utilization and outcomes for patients with renal cell carcinoma (RCC) and tumour thrombus (TT). Radical nephrectomy with thrombectomy is a standard treatment for patients with RCC and associated TT. Morbidity and mortality rates tend to correlate with aggressiveness of tumour and TT level. Methods Patients undergoing radical nephrectomy with thrombectomy (2006–2023) were retrospectively identified. Inclusion criteria included RCC histology and preoperative imaging available for thrombus‐level categorization based on the Mayo Clinic grading system. Logistic regression assessed predictors for utilizing CPB, and Cox regression identified factors associated with survival. Results A total of 72 patients with RCC and associated TT were identified. The median age was 67 years. RCC‐related symptoms were present in 83%, and 28% had Levels 3 and 4 thrombi. Eleven patients (15.3%) had undergone neoadjuvant therapy, and 81% had clear‐cell RCC. CPB was utilized in eight (11.1%) cases. The median tumour size was 10.5 cm. Metastatic disease was greater in the CPB cohort (75% vs. 28%, p = 0.008). All cases performed on CPB were Levels 3 and 4 thrombi (100% vs. 19% in the non‐CPB group, p < 0.001). CPB cases had significantly longer operative time, and hospital stays and rates of Clavien ≥ 3 complications. On multivariate analysis, metastatic disease was a predictor of CPB utilization. Median survival was 74 and 25 months in the non‐CPB and CPB cohorts, respectively (p = 0.01). Pulmonary disease and metastatic disease with CPB utilization were significantly associated with worse survival on multivariate analysis. Conclusions Surgical extirpation of kidney tumours with associated TT remains the standard of care among patients with locally advanced RCC. CPB can be utilized to increase the feasibility of resection for high‐level thrombi. Preoperative planning and cooperation among surgical teams are key given the perioperative morbidity and mortality.